Groundwater engineering - Tang, Yiqun; Zhou, Jie; Yang, Ping; Yan, Jingjing; Zhou, Nianqing (Springer environmental science and engineering,, 2016)
Integrating information from several areas of engineering geology, hydrogeology, geotechnical engineering, this book addresses the general field of groundwater from an engineering perspective. It covers geological engineering as well as hydrogeological and environmental geological problems caused by groundwater engineering. It includes 10 chapters, i.e., basic groundwater theory, parameter calculation in hydrogeology, prevention of geological problem caused by groundwater, construction dewatering, wellpoint dewatering methods, dewatering wells and drilling, groundwater dewatering in foundation-pit engineering, groundwater engineering in bedrock areas, numerical simulation in groundwater engineering, groundwater corrosion on concrete and steel. Based on up-to-date literature, it describes recent developments and presents several case studies with examples and problems. It is an essential reference source for industrial and academic researchers working in the groundwater field and can also serve as lecture-based course material providing fundamental information and practical tools for both senior undergraduate and postgraduate students in fields of geology engineering, hydrogeology, geotechnical engineering or to conduct related research.